2011
DOI: 10.1016/j.biopsych.2010.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Alterations in Adults with Attention-Deficit/Hyperactivity Disorder Identified by Voxel Based Morphometry

Abstract: Background Gray and white matter volume deficits have been reported in many structural magnetic resonance imaging (MRI) studies of children with attention-deficit/hyperactivity disorder (ADHD); however, there is a paucity of structural MRI studies of adults with ADHD. This study used voxel based morphometry and applied an a priori region of interest approach based on our previous work, as well as from well-developed neuroanatomical theories of ADHD. Methods Seventy-four adults with DSM-IV ADHD and 54 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
122
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(146 citation statements)
references
References 79 publications
(110 reference statements)
18
122
2
4
Order By: Relevance
“…These findings are in line with a well-powered study of ADHD that had controlled for affective dysfunctions (Seidman et al, 2011). In that study an increased volume of lObfc bilaterally and rACC was observed in ADHD patients compared with controls, in conjunction with the expected decreased volume in non-emotional attentional systems including dlPFC and cACC that has previously been welldescribed for ADHD patients.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These findings are in line with a well-powered study of ADHD that had controlled for affective dysfunctions (Seidman et al, 2011). In that study an increased volume of lObfc bilaterally and rACC was observed in ADHD patients compared with controls, in conjunction with the expected decreased volume in non-emotional attentional systems including dlPFC and cACC that has previously been welldescribed for ADHD patients.…”
Section: Discussionsupporting
confidence: 76%
“…There seems to be a link between structure and function in clinical states such as ADHD and BPD. For example, in ADHD, smaller GMV in dlPFC and cACC has been observed (Seidman et al, 2011), and these structures are less activated during attentional tasks in this group (Dickstein et al, 2006). Likewise, in BPD, smaller GMV has been observed in lObfc and rACC (Soloff et al, 2008(Soloff et al, , 2012 and these regions are less activated in emotional regulation for this group of patients (Wingenfeld et al, 2009;Schulze et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Here, the lack of significant finding in the basal ganglia may also be related to the characteristics of our ADHD sample, which included boys with no psychiatric comorbidity, no learning disorder and a mean IQ of 105.7. Indeed, high-functioning samples presumably exhibit more subtle brain alterations that may be difficult to detect at a corrected statistical thresholding (Seidman et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For region-of-interest-based (ROI) analyses we used ROIs from the cross-sectional study 33 based on an earlier study by Seidman and colleagues. 36 Because the GLM-flex toolbox does not allow small-volume correction for multiple comparisons within an ROI, we extracted all voxels from the ROIs and corrected for multiple comparisons using false discovery rate (FDR) correction across all voxels of the corresponding ROI. Figure 1 illustrates the selection process for the baseline sample.…”
Section: Criterion Of Significancementioning
confidence: 99%